2016
DOI: 10.1071/an14943
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bodyweight from body measurements and determination of body measurements on Limousin cattle using digital image analysis

Abstract: The objective of this study was to predict bodyweight and estimate body measurements of Limousin cattle using digital image analysis (DIA). Body measurements including body length, wither height, chest depth, and hip height of cattle were determined both manually (by measurements stick) and by using DIA. Body area was determined by using DIA. The images of Limousin cattle were taken while cattle were standing in a squeeze chute by a digital camera and analysed by image analysis software to obtain body measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The performance of the stepwise linear regression for LW was much poorer than the ANN (R 2 = 0.54, RMSE = 51). Ozkaya et al (2016) used multiple linear regression of measurements extracted from lateral 2D digital images of Limousin cattle to predict LW with an R 2 of 0.89. Although sex and breed type had low importance (3 and 0, respectively, Table 3), to investigate the performance of sex and breed specific models the ANN was trained only using the Aberdeen Angus steers data subset (n = 441, Table 1).…”
Section: Prediction Of Liveweight Cold Carcass Weight and Saleable Meat Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of the stepwise linear regression for LW was much poorer than the ANN (R 2 = 0.54, RMSE = 51). Ozkaya et al (2016) used multiple linear regression of measurements extracted from lateral 2D digital images of Limousin cattle to predict LW with an R 2 of 0.89. Although sex and breed type had low importance (3 and 0, respectively, Table 3), to investigate the performance of sex and breed specific models the ANN was trained only using the Aberdeen Angus steers data subset (n = 441, Table 1).…”
Section: Prediction Of Liveweight Cold Carcass Weight and Saleable Meat Yieldmentioning
confidence: 99%
“…As imaging technologies become more advanced and affordable it is now economically feasible to implement them on commercial farms. Ozkaya et al (2016) demonstrated that body measurements of cattle (body length, wither height, chest depth. and hip height) can be accurately determined from 2-dimensional (2D) digital image analysis (90-98% accuracy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement methods of livestock morphometric data were treated according to Ozkaya et al (2016). The BW data were obtained by weighing the animal on a 0.5 kilograms scale (Iconix FX-1, New Zealand) with a perpendicular position to the surface.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Body measurements in the animal studied consisted of body length (BL), withers height (WH) and heart girth (HG) as presented in Figure 3. According to Ozkaya et al (2016), data of BL was obtained by measuring the distance between the shoulder joint (later tuberosity of humerus) to the edge of the pelvic bone. Data of WH was obtained by measuring the distance from the withers to the surface by the perpendicular line.…”
Section: Body Measurements Body Weight and Ages Identificationmentioning
confidence: 99%